Research progress on layered seismic anisotropy - A review - Shengyi Shen; Yuan Gao (Earthquake Research Advances, 2021)
Seismic anisotropy is an effective feature to study the inner structure of the Earth. In complex tectonic area, the assumption of single-layer anisotropy is sometimes not well consistent with the observed data; thus, the assumption of multi-layered (i.e. stratified) anisotropy should be considered. At present, the main methods to study anisotropy include receiver functions, shear wave splitting from local and teleseismic events (SKS, SKKS, and PKS, hereafter collectively called XKS), P- and Pn wave travel time inversion, surface wave inversion from far-field earthquakes and ambient noise. Each of the above method has its own advantages and limitations. Thus, one or more of the above methods are often combined to characterize multi-layered anisotropy, of which the depth range of anisotropic layers are different. This paper reviews the research progress of multi-layered anisotropy for the purpose of providing a basis for future seismic anisotropy investigations.